2020
DOI: 10.5152/addicta.2020.19125
|View full text |Cite
|
Sign up to set email alerts
|

Results of Smoking Cessation Clinic in Erenköy Mental and Neurological Diseases Training and Research Hospital: An Investigation Into the Effects of Cognitive Behavioral Intervention and Pharmacotherapy

Abstract: Addicta: The Turkish Journal on Addictions is an international, scientific, open access periodical published in accordance with independent, unbiased, and double-blinded peer-review principles. The journal is the official publication of Türkiye Yeşilay Cemiyeti (Turkish Green Crescent Society), and it is published quarterly in January, May, September, and December. The publication language of the journal is English.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Two international studies found a lower rate of quitting smoking in individuals with a low socioeconomic level and low educational level (17,18). Other studies have found no difference between smoking cessation status and educational level (1,2,12,14,15). Some studies found no difference between smoking cessation status and working status (2,12).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Two international studies found a lower rate of quitting smoking in individuals with a low socioeconomic level and low educational level (17,18). Other studies have found no difference between smoking cessation status and educational level (1,2,12,14,15). Some studies found no difference between smoking cessation status and working status (2,12).…”
Section: Discussionmentioning
confidence: 99%
“…When smoking cessation and sociodemographic characteristics were evaluated, one study found a high frequency of smoking cessation in men, while other studies have found no difference between gender and smoking cessation status (1,2,(12)(13)(14)(15). The relationship between the age of individuals and their smoking cessation success is controversial in studies (1,2,14,15).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations